(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Water remains the most abundant and critical commodity for guaranteeing the continuity of human lives on earth. Ensuring cleanliness of water for human consumption is of paramount importance. The 222Rn concentration has been assessed in drinking water samples collected from various water resources used by communities around Sokoto Cement Company, with the view of assessing the radiological risk, if any, to human health. The sources of collected water samples were hand pumps and hand dug wells and water seepages. Determination of radon concentration was conducted using liquid scintillation counter (Model: Tri-Carb-LSA1000) following standard procedures. The overall mean value of 222Rn concentration was found to be 34±3.7 Bq/L The resulting mean annual effective doses due to inhalation of radon in the water samples was 41 μSvy-1, while ingestion for adults, children and infants were 248±27 μSvy-1, 372±40 μSvy-1 and 434±47 μSvy-1 respectively. These values are above the recommended benchmarks prescribed by UNSCEAR, WHO, European commission and USEPA guiding the utilization of water for drinking and domestic purposes. This indicates that the water resources around the cement company are not safe for drinking and domestic purposes from the radiological point of view.